SrBi2Ta2O9 ferroelectric thick films prepared by electrophoretic deposition using aqueous suspension - Zanetti, S. M.; Varela, José Arana [UNESP]; Leite, E. R.; Longo, Elson [UNESP] (Elsevier B.V., 2004)
SrBi2Ta2O9 ferroelectric thick films were prepared by electrophoretic deposition (EPD). For that, ceramic powders were prepared by chemical method in order to obtain compounds with chemical homogeneity. The polymeric precursor method was used for the synthesis of the SrBi2Ta2O9 powder. The crystallographic structure of the powder was examined by X-ray diffraction, and the surface area was determined by single point BET adsorption. The 0.03 vol.% suspension was formed by dispersing the powder in water using two different polymers as dispersants: an ester polyphosphate (C213) and an ammonium polyacrilate (Darvan 821-A). It was investigated the influence of the different dispersants in the surface properties of the powder by zeta potential measurements. The films were deposited on platinum-coated alumina and Pt/Ti/SiO2/Si substrates by a 4 mA constant current, for 10 min, using two parallel electrodes placed at a separation distance of 3 min in the suspension. Several cycles of deposition-drying of the deposit were carried out until reaching the desired thickness. After thermal treatment at temperatures ranging from 700 to 1000 degreesC, the films were characterized by X-ray diffraction and scanning electron microscopy for the microstructure observation. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: electrophoresis; ferroelectric properties; SBT; SrBi2Ta2O9; suspensions; tantalates; thick films